Internationalization process and decision-making: An approach through the lens of the manager cognition - VLAČIĆ, Božidar (2017)
The influence of several environmental and organizational factors on the decision making process of international business-IB have been extensively investigated over the last decades. However, the micro-foundations of the cognitive features of the decision maker and their impact on the organization’s strategic decisions are still an unexplored area when discussing the process of internationalization. In this paper, this internationalization process decision making is examined under the umbrella of the intertwined relations between environment, organization and manager’s cognitive style. The aim of this paper is to reflect of the role of the manager’s cognitive style on the process of filtering information from the international business environment in order to create better internationalization strategic decisions. Under the socio-cognitive approach of the dual-process theory, this study explores the role of System-X (emotional, intuitive, automatic reasoning) and System-C (analytical, conscious, deliberate reasoning) on the IB decision making process. Finally, we open future research avenues for digging deeper in the multileveled association between IB environmental features, organization, manager’s cognitive style and internationalization mode.